Development of a poetic corpus based on Abai's poems (Eurasian Journal of Philology Science and Education, 2024)
The scientific article is devoted to the creation of a poetic corpus based on Abai’s poems and his contribution to corpus linguistics. The purpose of the study is to create a structural linguistic fund that allows for a more in-depth analysis of the linguistic features of the texts of Abai’s poems in the course of developing a poetic corpus based on Abai’s poems. The work has great theoretical and practical significance in the study of the Kazakh language and culture. The reason is that by putting poetic marks on Abai's poems, we can see the extent of the use of the Kazakh language during Abai's time, changes in the language and cultural relations of that time, and also study the poet's language from a linguistic point of view. and poetic point of view. The research methodology includes corpus linguistics and computer modeling, which allow objective analysis of texts. If a poetic corpus is developed on the basis of Abai's poems, referring to the conditions of corpus linguistics, the poetic notation of Abai's poems is carried out through computer modeling. Models associated with conventional signs are implemented on the basis of language and software algorithms. The main findings suggest that changes in Abai's language and style can be systematized and further studied. The study makes a major contribution to linguistics and expands the possibilities of analysis and interpretation of poetic texts. The practical significance of the work lies in the creation of programs and tools for teaching and researching the Kazakh language based on the analysis of literary texts.Keywords: corpus linguistics, poetic corpus, poetic notation, computer modeling, cultural heritage, educational resources.